ANALISIS AFIKSASI VERBA PADA TEKS BACAAN DALAM BUKU BAHASA INDONESIA KELAS VIII - Aulia Zalsabilah Said; Sulastriningsih Sulastriningsih; Nurhusna Nurhusna (Titik Dua: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Analysis Of Affixation Verb In Reading Text Indonesia Book Clas VIII. The study aims to: (1) Describe the form of verb affixation in the reading text of Indonesian language books for clas VIII, (2) Describe meaning of verb affixation in the reading texts of Indonesian books for class VIII. This type of research is qualitative research using descriptive method.  The data sources in this study were obtained from reading texts in the revised 2017 edition of the Indonesian language book class VIII by Suherli et al. The techniques used in data collection are reading, identification, and classification techniques. The results of this study found that verb affixation consist of: 1) prefixes: men-, ke-, di-, meng-, ter-, se-, and ber-; 2) the suffixes –an, -kan, and –i; and 3) confixes of ber-an, ber-kan, ke-an, pe-an, and se-nya. The meaning of verb affixation found is grammatical meaning because the process of word formation can result in changes in meaning. The grammatical meaning is formed because of the grammaticalization process such as giving affixes (affixes), reduplication (repetition), or compounding words so that the basic word become compound words.